The contemporary management of prostate cancer - Deep Chakrabarti; Peter Albertsen; Aidan Adkins; Amar Kishan; Vedang Murthy; Chris Parker; Angela Pathmanathan; Alison Reid; Oliver Sartor; Nicholas Van As; Jochen Walz; Alison Tree (CA: A Cancer Journal for Clinicians, 2025)
Abstract Prostate cancer is the most common cancer in two thirds of the world, with an expected doubling in both incidence and mortality in the next two decades. No strong environmental associations exist for the development of prostate cancer; therefore, lifestyle measures are unlikely to mitigate this increasing burden. The last three decades have seen rapid developments in the diagnostic and therapeutic landscape of prostate cancer, including multiparametric magnetic resonance imaging, positron emission tomography, robotic surgery, image‐guided hypofractionated and stereotactic radiotherapy, novel anti‐androgens and radioligand therapies. Prostate cancer is unique in that not everyone with a diagnosis needs treatment, and active surveillance is the preferred option for some. This review discusses the contemporary management of all stages of prostate cancer in the light of these modern developments, enabling holistic individualization of treatment, and describes the promise of future research to further improve outcomes.